2013
DOI: 10.1038/mp.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

708 Common and 2010 rare DISC1 locus variants identified in 1542 subjects: analysis for association with psychiatric disorder and cognitive traits

Abstract: A balanced t(1;11) translocation that transects the Disrupted in schizophrenia 1 (DISC1) gene shows genome-wide significant linkage for schizophrenia and recurrent major depressive disorder (rMDD) in a single large Scottish family, but genome-wide and exome sequencing-based association studies have not supported a role for DISC1 in psychiatric illness. To explore DISC1 in more detail, we sequenced 528 kb of the DISC1 locus in 653 cases and 889 controls. We report 2718 validated single-nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 73 publications
1
56
1
Order By: Relevance
“…This novel locus may interact directly with DISC1 , a possible schizophrenia 37,38 and OD 2,31 risk gene whose protein product has a role in cognitive function. 39 Additionally, we added to the already considerable evidence for association of variants in the ADH alcohol-metabolizing enzyme genes to AD. Further studies are needed to confirm these associations and to elucidate the functional relationships of the several novel risk loci we identified to AD.…”
Section: Discussionmentioning
confidence: 99%
“…This novel locus may interact directly with DISC1 , a possible schizophrenia 37,38 and OD 2,31 risk gene whose protein product has a role in cognitive function. 39 Additionally, we added to the already considerable evidence for association of variants in the ADH alcohol-metabolizing enzyme genes to AD. Further studies are needed to confirm these associations and to elucidate the functional relationships of the several novel risk loci we identified to AD.…”
Section: Discussionmentioning
confidence: 99%
“…A t(1;11) translocation revealed genomewide significant linkage for schizophrenia, rMDD and together with BD (Thomson et al, 2014). DISC1, translin-associated factor X (TSNAX) and D-amino acid oxidase activator (DAOA) were supposed to play a role as DISC1-TSNAX variants in MDD susceptibility (Arias et al, 2014).…”
Section: Lncrnas Related To Synaptic Plasticity Potentially Associatementioning
confidence: 99%
“…Up to 2012, more than 350 million people suffer from depression all over the world, patients suffering from major depressive disorder (MDD) will get a 12-month prevalence of 6.6% and a lifetime prevalence of 16.2%, and women are twice susceptible compared to men (Thomson et al, 2014). Compared to unipolar depression patients, bipolar patients are much more likely to present to clinicians, while unipolar depression is more prevalent than bipolar disorder (Hirschfeld, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it might significantly contribute to cell cycle abnormalities as well as to deficits in oligodendroglial cell differentiation and maturation found in schizophrenia. of evidence has accumulated pointing toward disruptedin-schizophrenia 1 (DISC1) as a candidate gene that influences risk of schizophrenia and other mental disorders (overview in [25]). DISC1 codes for a major protein of about 100 kDa and various, yet incompletely characterized isoforms generated by alternative splicing [26].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that DISC1 plays important roles during neurodevelopment, including neuronal proliferation, neurite outgrowth, neuronal migration, and synapse formation, all implicated in the pathophysiology of schizophrenia (reviewed in [27]). Furthermore, genetic variants of DISC1 were shown to be associated with the hippocampal volume [28], cortical thickness [29], and prefrontal-associated cognition [25]. DISC1 protein is predominantly localized in neurons ( [30] and many others), but there is also evidence for a wide extra-neuronal expression (i.e., in cultured astrocytes, OLs, microglia, and radial progenitor cells, [1,23,[31][32][33]).…”
Section: Introductionmentioning
confidence: 99%